Biofouling potential and material reactivity in a simulated water distribution network supplied with stormwater recycled via managed aquifer recharge. (15th November 2016) - Gonzalez, Dennis; Tjandraatmadja, Grace; Barry, Karen; Vanderzalm, Joanne; Kaksonen, Anna H.; Dillon, Peter; Puzon, Geoff J.; Sidhu, Jatinder; Wylie, Jason; Goodman, Nigel; Low, Jason
Abstract: The injection of stormwater into aquifers for storage and recovery during high water demand periods is a promising technology for augmenting conventional water reserves. Limited information exists regarding the potential impact of aquifer treated stormwater in distribution system infrastructure. This study describes a one year pilot distribution pipe network trial to determine the biofouling potential for cement, copper and polyvinyl chloride pipe materials exposed to stormwater stored in a limestone aquifer compared to an identical drinking water rig. Median alkalinity (123 mg/L) and colour (12 HU) in stormwater was significantly higher than in drinking water (82 mg/L and 1 HU) and pipe discolouration was more evident for stormwater samples. X-ray Diffraction and Fluorescence analyses confirmed this was driven by the presence of iron rich amorphous compounds in more thickly deposited sediments also consistent with significantly higher median levels of iron (∼0.56 mg/L) in stormwater compared to drinking water (∼0.17 mg/L). Water type did not influence biofilm development as determined by microbial density but faecal indicators were significantly higher for polyvinyl chloride and cement exposed to stormwater. Treatment to remove iron through aeration and filtration would reduce the potential for sediment accumulation. Operational and verification monitoring parameters to manage scaling, corrosion, colour, turbidity and microbial growth in recycled stormwater distribution networks are discussed. Graphical abstract: Highlights: Higher alkalinity and iron in stormwater resulted in greater sediment deposition. Pipe hues differed due to varying source water concentrations of iron and copper. Sediment and biofilm accumulation limited by sloughing cycle. Microbial cell counts were similar in stormwater and drinking water pipes.